Poverty alleviation and sector development - Okalang, Kenneth (2008)
The study analyses the linkage between an increase in a sector's growth of output and poverty alleviation. A multiplier decomposition method shows the linkages through which a productions sector's output contributes to poverty alleviation. The empirical data of the thesis is based on a socioeconomic system represented by the 1999 Social accounting Matrix (SAM) for Uganda. It is shown that a multiplier can be broken down into two multiplicative effects. Firstly, the distributional effects where the impact of a sector's output on poverty alleviation can be direct through incomes to the poor households from their labor or land to the sector's grow of output. Secondly, the interdependency effects which results from the indirect effects operating through the interdependence of economic activities sometimes called the closed loop effect. The decomposition method shows that growth in agriculture alleviates poverty among poor households, followed then by the services sector and the industry sectors. The policy implication is that the process of industrialization involves moving the bulk of the labor force from the agricultural sector to the industry sector and this can be enhanced by education and training.